PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Studi empiris pada perusahaan manufaktur yang terdaftar di BEI tahun 2010-2012) (Students' Journal of Accounting and Banking, 2014)
This study aimed to examine the effect of CSR, managerial ownership, foreign ownership, independent board, board of directors, audit committee, and firm size on corporate performance in the companies listed in Indonesia Stock Exchange.The population in this study were 133 companies listed on the Indonesia Stock Exhangein 2010-2012. The sample purposive samling as many as 18 company. Mechanical testing data is to use a multiple linear regression analysis.The analysis showed that CSR, managerial ownership, foreign ownership, independent board, board of directors, audit committee, and the size of the company does not have a significant effect on corporate performance.Keywords: CSR, managerial ownership, foreign ownership, independent board, board of directors, audit committee, firm size, and firm performance